SOSIALISASI AKSI SOSIAL PEMBERSIHAN LINGKUNGAN DI DESA JARING HALUS - Anisa Noverita; Eka Darliana; Trysanti Kisria Darsih; Kahar Mashuri; Zulham Siregar; Yusda Novianti; Deni Hartanto; Sakura Alwina (Jurnal Pengabdian Kepada Masyarakat, 2022)
The environment for humans is one of the most important elements in their lives, because the environment is not only a place for humans to move, but the environment also plays a very important role in supporting various human activities. In the environment, all human needs are available so that there are efforts made by humans to exploit their environment for their livelihood. Therefore, it is natural that human interaction with the environment will take place continuously and continuously. With this interaction, it is certain that environmental conditions will also be influenced by human behavior. Human attitudes and behavior will determine the good and bad conditions of an environment. Environmental cleanliness has a very important and inseparable role in human life. What is meant by environmental cleanliness is creating a healthy environment so that it is not susceptible to various diseases. This community service is carried out in Jaring Halus Village, Secanggang District, Langkat Regency, North Sumatra Province. The method of implementing this community service is socialization and social action. The results of this community service are increasing public knowledge about the importance of cleanliness and environmental sustainability as well as increasing their responsibility and participation in keeping the environment clean, healthy and sustainable in Jaring Halus Village so that it is hoped that the community can continue to realize it in everyday life.